Multiscale simulations and mechanics of biological materials - Li, Shaofan; Qian, Dong. (Somerset, N.J. : Wiley, 2013)
Multiscale Simulations and Mechanics of Biological Materials A compilation of recent developments in multiscale simulation and computational biomaterials written by leading specialists in the field Presenting the latest developments in multiscale mechanics and multiscale simulations, and offering a unique viewpoint on multiscale modelling of biological materials, this book outlines the latest developments in computational biological materials from atomistic and molecular scale simulation on DNA, proteins, and nano-particles, to meoscale soft matter modelling of cells, and to macroscale soft tissue and blood vessel, and bone simulations. Traditionally, computational biomaterials researchers come from biological chemistry and biomedical engineering, so this is probably the first edited book to present work from these talented computational mechanics researchers. The book has been written to honor Professor Wing Liu of Northwestern University, USA, who has made pioneering contributions in multiscale simulation and computational biomaterial in specific simulation of drag delivery at atomistic and molecular scale and computational cardiovascular fluid mechanics via immersed finite element method. Key features: -Offers a unique interdisciplinary approach to multiscale biomaterial modelling aimed at both accessible introductory and advanced levels -Presents a breadth of computational approaches for modelling biological materials across multiple length scales (molecular to whole-tissue scale), including solid and fluid based approaches -A companion website for supplementary materials plus links to contributors' websites (www.wiley.com/go/multiscale).
pt. 1. Multiscale simulation theory -- pt. 2. Patient-specific fluid-structure interaction modeling, simulation and diagnosis -- pt. 3. From cellular structure to tissues and organs -- pt. 4. Bio-mechanics and materials of bones and collagens.
Includes bibliographical references and index.
Keywords: Biomechanics; Multiscale modeling; TECHNOLOGY & ENGINEERING -- Materials Science; Biomechanics; Multiscale modeling; Electronic books